PEDAGOGIKA FANINING YARATILISH TARIXI VA BOSHQA FANLAR BILAN ALOQADORLIK XUSUSIYATLARI - Marayimova Kibriyoxon Islomjon qizi, Muhammadjonova O‘giloy Bahodirjon qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, information about the science of pedagogy and scientists who made a great contribution to the science of pedagogy and the relationship of this science with other disciplines and the history of injury are given, and information is also given about the goals and tasks of the science of pedagogy. passed.